1991
DOI: 10.1111/j.1525-1470.1991.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Papular Acrodermatitis of Childhood (Gianotti‐Crosti Disease)

Abstract: An 11-year-old boy had lentil-sized lichenoid papules, localized to the limbs and trunk, together with acute, nonicteric, hepatitis B surface antigen-positive hepatitis. The clinical picture and course were typical of Gianotti-Crosti disease. Monoclonal antibodies were used to study the lymphocyte subpopulations and surface antigens in the inflammatory infiltrate in frozen sections of a skin biopsy specimen. The results provide data on the pathogenic mechanism of the papular exanthem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Viral infections are J AM ACAD DERMATOL VOLUME 54, NUMBER 1 still the key factor and many have postulated an infectious-allergic pathway. 32,33 The major HBV subtypes are adr, ayr, adw, and ayw; the last two are most common in Europe, 34 but the ayw subtype from southern Europe is most often connected with GCS. 9,11 In contrast, in southeast Asia the responsible subtypes are usually adr and adw.…”
Section: Originmentioning
confidence: 99%
“…Viral infections are J AM ACAD DERMATOL VOLUME 54, NUMBER 1 still the key factor and many have postulated an infectious-allergic pathway. 32,33 The major HBV subtypes are adr, ayr, adw, and ayw; the last two are most common in Europe, 34 but the ayw subtype from southern Europe is most often connected with GCS. 9,11 In contrast, in southeast Asia the responsible subtypes are usually adr and adw.…”
Section: Originmentioning
confidence: 99%
“…Although this site is uncommon, a sparse truncal distribution has been reported in previous cases. 3,15 Both patients exhibited pale, perilesional halos about several of the lesions. Although perilesional pallor does occur in a range of other dermatoses, including pruritic and urticated papules and plaques of pregnancy and idiopathic juvenile arthritis, it does not appear to have been previously described in classical GCS.…”
Section: Discussionmentioning
confidence: 97%
“…The pathogenic mechanism remains unknown but it is believed to be an immune-mediated process requiring prior stimulation by immunization, viral or bacterial infection. 3,4 The initial reports of GCS were related to hepatitis B infection in children; however, a diverse range of associations is now recognized (Table 1). 1,2 Epstein-Barr virus (EBV) is now considered the most common association in the USA, perhaps due to hepatitis B immunization.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This delayed type of T cell immune response can be induced by a number of chemical and physical stimuli or pathogens. In this regard, Magyarlaki et al suggested virusinduced type IV cutaneous hypersensitivity (15).…”
Section: Gcs Shows Characteristic Cutaneous Eruption Following Viral mentioning
confidence: 99%